Endovascular treatment of ruptured and unruptured intracranial dissecting aneurysms - Dr.DMRD Saima Ahmad (Interdisciplinary Neurosurgery, 2019)
Objectives: Dissecting aneurysms are rare as contrasted with their saccular counterparts, yet they stay hard to treat and are related with high rates of rebleeding and morbidity. Material & methods: In this study, we have reviewed dissecting aneurysms of both anterior and posterior circulation, both ruptured and unruptured, including natural history, endovascular treatment and clinical outcome. They account for 3–7% of cases of nontraumatic subarachnoid hemorrhage. Surgical treatment carries a significant risk of neurological complications predominantly lower cranial nerve deficits because of the close relationship of the posterior circulation aneurysm with the brain stem and cranial nerves. Results: A total of 28 ruptured and unruptured dissecting aneurysms in both anterior and posterior circulation were treated endovascularly from January 2015 till October 2018. Out of 28, 23 of the aneurysms were in posterior circulation and 5 were in anterior circulation. All the cases were technically successful except in 1 case. Procedure related complications were seen in 9 patients which were transient except in one patient who died. Follow up studies showed stable and complete occlusion of aneurysms in all patients except in 1 case in which recanalization was seen. Conclusion: Dissecting aneurysms are dynamic lesions with variable and unpredictable evolution and a through treatment is warranted. Endovascular treatment by coiling and parent artery occlusion is relatively safe and effective treatment of dissecting intracranial aneurysms. Keywords: Dissecting aneurysms, Ruptured aneurysms, Endovascular, Aneurysms